Philosophy of Material Logics Learning Tauhid the Nature of Two-Twenty Work Habib Usman bin Yahya in Islamic Religion Education - Nurhadi Nurhadi (Pendidikan Agama Islam STIT Palapa Nusantara, 2019)
Aqidah Tauhid is belief and knowledge which addresses the form of God, the obligatory nature, the nature of jaiz and the impossible nature. Islam among complete religions teaches Tawheed ahlisunnah waljama'ah, in the frame of ‘Asy’ariyah Maturidiyah, which contains the characteristics of twenty charities ma'rifah, because awaluddin ma'rifatullah